Controlled biosynthesis of curdlan oligosaccharides with tunable degree of polymerization and their prebiotic effects on gut microbiota - Yaping Pan; Yuying Wang; Zhilei Liu; Tong Liang; Zepeng Chang; Qingyu Wang; Qijun Pan; Yun Jiang; Zhitao Li; Minjie Gao (Bioresource Technology, 2026)

Sub-chronic copper exposure alters growth performance, intestinal histopathology, and intestinal microbiota in adult zebrafish (Danio rerio) - Yaping Wang; Yaqian Fu; Xuyang Zhai; Chang Dong; Mengdie Yang; Ziyi Huang; Fei Liu (Ecotoxicology, 2026)

Ectomycorrhizal and saprotrophic fungi are linked to reduced pathogenic fungi across roots and rhizosphere soils of major afforestation species in northeastern China - Wen Guo; Xiangxia Yang; Yaping Liu; Xiaoding Lin; Le Chang; Yaru Wei; Mingming Xia; Minghao Lv; Kazuo Isobe (Soil Ecology Letters, 2026)

Characterisation of ginsenosides composition in processed American ginseng products using UPLC-MS coupled with chemometric analysis - Chang Wang; Xiaolei Tang; Haiyu Chen; Yaping Wang; Xitong Yuan; Daqing Zhao; Baotai Huang; Li Liu; Bin Qi (Natural Product Research, 2026)

Synthetic pertinence clustering and reinforced evolutionary algorithm for the hybrid E-commerce green location routing problem - Chang Lv; Chaoyong Zhang; Yaping Ren; Leilei Meng; Jianzhao Wu (Swarm and Evolutionary Computation, 2026)

Quantifying glacier and snow shrinkage: future water stress in Northern Tien Shan, Central Asia - Qiudong Zhao; Yongjian Ding; Zizhen Jin; Yan Qin; Rui He; Donghui Shangguan; Shiqiang Zhang; Yaping Chang; Haidong Han (CATENA, 2026)

Preparation and application of the transistor based on D-A isoindigo copolymer/GR blend for the detection of circular tumor cell - Caiyuan Liao; Fayu Wang; Long Fang; Rong Zou; Yaping Wang; Gang Chang; Hanping He (Analytica Chimica Acta, 2026)

A graph Fourier Kolmogorov-Arnold Network (G-FourierKAN) and its application to spring discharge simulation - Yaping Yin; Xingchao Deng; Huiqing Hao; Yonghong Hao; Huibin Chang; Tian-Chyi Jim Yeh (Journal of Hydrology, 2026)

Simultaneously promoting gellan lyase expression and gellan oligosaccharide production by gellan gum co-feeding during Pichia pastoris fermentation - Tong Liang; Yuying Wang; Feiyang Duan; Yaping Pan; Zepeng Chang; Qijun Pan; Yun Jiang; Zhitao Li; Minjie Gao (Systems Microbiology and Biomanufacturing, 2026)

Condition assessment of corroded spanning subsea pipelines under vortex-induced vibration - Xinhong Li; Runquan Li; Yaping Hu; Ziyue Han; Xiuquan Liu; Yuanjiang Chang (Ocean Engineering, 2025)

Plasma-catalytic reforming of CO2–CH4 over nickel-based catalysts: Catalyst design, plasma activation, and comparison of different catalytic systems - Tian Chang; Xuanchen Chang; Zuotong Zhao; Chuanlong Ma; Xiangen Zhao; Yaping Du; Antonio Otavio T. Patrocinio; Anton Nikiforov; Chuanyi Wang (Journal of Environmental Chemical Engineering, 2025)

Associations Between Organophosphate Esters Exposure and Metabolic Syndrome: Exploring the Mediating Role of Oxidative Stress and Inflammation in Adults - Sijie Yang; Yaping Li; Ling Liu; Zhengce Wan; Qitong Xu; Chang Xie; Lulu Song; Youjie Wang; Hui Chen; Surong Mei (Exposure and Health, 2025)

Effective identification of debris-covered glaciers in Western China using multiple machine-learning algorithms - Rui He; Donghui Shangguan; Qiudong Zhao; Shiqiang Zhang; Zizhen Jin; Yan Qin; Yaping Chang (Science of The Total Environment, 2024)

Individual and joint effects of organophosphate esters and hypertension or diabetes on renal injury among Chinese adults - Sijie Yang; Yaping Li; Mingye Zhang; Qitong Xu; Chang Xie; Zhengce Wan; Lulu Song; Yongman Lv; Youjie Wang; Hui Chen; Surong Mei (International Journal of Hygiene and Environmental Health, 2024)

Contribution of climatic variables and their interactions to reference evapotranspiration changes considering freeze-thaw cycles in the Tibetan Plateau during 1960–2022 - Yaping Chang; Yongjian Ding; Shiqiang Zhang; Donghui Shangguan; Jia Qin; Qiudong Zhao (Atmospheric Research, 2024)

Association between organophosphate esters individual and mixed exposure with the risk of hyperlipidemia and serum lipid levels among adults in Wuhan, China - Qitong Xu; Chang Xie; Sijie Yang; Yaping Li; Mingye Zhang; Zhengce Wan; Lulu Song; Yongman Lv; Hui Chen; Youjie Wang; Surong Mei (Environmental Science and Pollution Research, 2024)

Associations of exposure to organochlorine pesticides and polychlorinated biphenyls with chronic kidney disease among adults: the modifying effects of lifestyle - Chang Xie; Sijie Yang; Yaping Li; Mingye Zhang; Qitong Xu; Zhengce Wan; Lulu Song; Yongman Lv; Dan Luo; Qiang Li; Youjie Wang; Hui Chen; et al. (Environmental Science and Pollution Research, 2024)

Quantifying the response of runoff to glacier shrinkage and permafrost degradation in a typical cryospheric basin on the Tibetan Plateau - Yaping Chang; Yongjian Ding; Shiqiang Zhang; Qiudong Zhao; Zizhen Jin; Jia Qin; Donghui Shangguan (CATENA, 2024)

Research on the spatiotemporal evolution and influencing factors of urbanization and carbon emission efficiency coupling coordination: From the perspective of global countries - Dalai Ma; Yin Yan; Yaping Xiao; Fengtai Zhang; Haoran Zha; Ruonan Chang; Jiawei Zhang; Zuman Guo; Bitan An (Journal of Environmental Management, 2024)

MiR-7 deficiency promotes Th1 polarization of CD4+T cells and enhances the antitumor effect in adoptive cell therapy for lung cancer - Xian Chang; Juanjuan Zhao; Ya Zhou; Mengmeng Guo; Yaping Yan; Ya Wang; Xu Zhao; Jing Yang; Chao Chen; Lin Tang; Ming Qin; Lin Xu (Immunologic Research, 2024)

Proteomic analysis of uterine lavage fluid of dairy cows at different time after delivery by mass spectrometry - Xingcan Jiang; Ziyuan Li; Xiyu Chang; Cong Huang; Rendong Qiu; Aihua Wang; Pengfei Lin; Keqiong Tang; Huatao Chen; Dong Zhou; Yaping Jin (Theriogenology, 2023)

Fine and coarse particulate air pollution and out-of-hospital cardiac arrest onset: a nationwide case-crossover study in China - Chang Pan; Chang Xu; Jiaqi Zheng; Ruixue Song; Chuanzhu Lv; Guoqiang Zhang; Huiqiong Tan; Yu Ma; Yimin Zhu; Xiaotong Han; Chaoqian Li; Shengtao Yan; et al. (Journal of Hazardous Materials, 2023)

Elevation‐dependent changes in the trend of reference evapotranspiration in the Tibetan Plateau during 1960–2017 - Yaping Chang; Yongjian Ding; Qiudong Zhao; Jia Qin; Shiqiang Zhang (International Journal of Climatology, 2023)
Elevation plays a crucial role in modulating the spatiotemporal distributions of climatic variables in mountainous regions, which affects water and energy balances, among which reference evapotranspiration (ET 0 ) is a key hydrological indicator. However, the response of ET 0 to climate change with elevation continues to be poorly understood, especially in the Tibetan Plateau (TP) which has elevation variations of more than 4,000 m. The spatiotemporal variations of ET 0 with elevation were investigated using long‐term (1960–2017) meteorological observations from 82 stations on the TP. The results suggest that the average annual ET 0 showed an insignificant increasing trend. A significant negative correlation between ET 0 and elevation was found ( p 0 decreased with elevation, whereas the negative trends of ET 0 increased significantly with elevation ( p 0 becomes smaller at higher‐elevation stations. Sensitivity analysis indicated that ET 0 was most sensitive to shortwave radiation ( R s ). Moreover, the sensitivities of temperature ( T ) and wind speed ( U ) significantly decreased with elevation, whereas those of R s and vapour pressure deficit (VPD) increased slightly with elevation. The contribution and path analyse indicated that increasing VPD was the dominant contributor to the increase in ET 0 . The effect of elevation on ET 0 variation mainly depended on the tradeoff between the contributions of U and VPD. U was the largest contributing factor for the change in ET 0 below 2,500 m, whereas VPD was the primary contributor to the increase in ET 0 above 2,500 m. This study provides insights into the response of ET 0 to climate change with elevation on the TP, which is of great significance to hydrometeorological processes in high‐altitude regions.

A 10-miRNA risk score-based prediction model for pathological complete response to neoadjuvant chemotherapy in hormone receptor-positive breast cancer - Chang Gong; Ziliang Cheng; Yaping Yang; Jun Shen; Yingying Zhu; Li Ling; Wanyi Lin; Zhigang Yu; Zhihua Li; Weige Tan; Chushan Zheng; Wenbo Zheng; et al. (Science China Life Sciences, 2022)

Conversion of organics and minerals into electricity and microalgae using a dual-membrane cylinder photo-microbial fuel cell - Gang Li; Haixing Chang; Yajun Zou; Jianzhi Yue; Yaping Zheng; Haowen Feng; Haihua Wu; Wenbo Wu; Jie Lou; Xueqiang Qi; Xingran Zhang (Environmental Chemistry Letters, 2021)

Fingolimod alters inflammatory mediators and vascular permeability in intracerebral hemorrhage - Yu-Jing Li; Guo-Qiang Chang; Yuanchu Liu; Ye Gong; Chunsheng Yang; Kristofer Wood; Fu-Dong Shi; Ying Fu; Yaping Yan (Neuroscience Bulletin, 2015)

The influence of vegetation variation on Northeast Asian dust activity - Rui Mao; Chang-Hoi Ho; Song Feng; Dao-Yi Gong; Yaping Shao (Asia-Pacific Journal of Atmospheric Sciences, 2013)

The Polymorphism of DNA Repair Gene ERCC2/XPD Arg156Arg and Susceptibility to Breast Cancer in a Chinese Population - Jiaoyang Yin; Duohong Liang; Ulla Vogel; Yaping Chang; Zhengrong Liu; Li Yue; Xiaoling Sun; Rong Qi; Tiehua Song (Biochemical Genetics, 2009)